Evidence of L-mode electromagnetic wave pumping of ionospheric plasma near geomagnetic zenith - Leyser, Thomas B; James, H Gordon; Gustavsson, Björn Johan; Rietveld, Michael T (Annales Geophysicae, 2018)
Publisher's version, source at: https://doi.org/10.5194/angeo-36-243-2018 The response of ionospheric plasma to pumping by powerful HF (high frequency) electromagnetic waves transmitted from the ground into the ionosphere is the strongest in the direction of geomagnetic zenith. We present experimental results from transmitting a left-handed circularly polarized HF beam from the EISCAT (European Incoherent SCATter association) Heating facility in magnetic zenith. The CASSIOPE (CAScade, Smallsat and IOnospheric Polar Explorer) spacecraft in the topside ionosphere above the F-region density peak detected transionospheric pump radiation, although the pump frequency was below the maximum ionospheric plasma frequency. The pump wave is deduced to arrive at CASSIOPE through L-mode propagation and associated double (O to Z, Z to O) conversion in pump-induced radio windows. L-mode propagation allows the pump wave to reach higher plasma densities and higher ionospheric altitudes than O-mode propagation so that a pump wave in the L-mode can facilitate excitation of upper hybrid phenomena localized in density depletions in a larger altitude range. L-mode propagation is therefore suggested to be important in explaining the magnetic zenith effect.